Hybridity and Identity in Rudolfo Anaya’s Bless Me, Ultima 1972 - Sid ,Racha; Kourdourli ,Abdelkader (University of Ammar Theledji -Laghouat, 2021)
Postcolonial studies have shed light upon hybridity and its considerable impact on the individuals’ psyche. Cultural identity, in particular, has aroused intense in social studies. On the other hand, the third space has become the basis for Mexican-Americans to construct their cultural identity and realize how unique and important they are in a contradictory society. This dissertation aims to explore and study how hybridity and other social circumstances formulate identity, essentially, Chicanos’ identity. Additionally, it attempts to investigate hybridity and cultural clash and their contributions to the construction of identity in Bless me, Ultima as a Chicano narrative. In three chapters, this study examines Antonio’s quest for identity, how he deals with his parents’ lifestyles as well as how he is able or unable to assimilate to the new environment centred on Anglo-American culture either by adopting a hybrid identity or retaining his Hispanic cultural identity